Increasing the Dimensionality of Modular Domino Reactions Triggered by Oxidative Cleavage: A Two‐Step Protocol Towards a Variety of Stereodefined Complex Oxygen Heterocycles1. Issue 12 (5th March 2013) - Castillo, Rafael R.; Abet, Valentina; Aquino, Maurizio; Gandara, Zoila; Retailleau, Pascal; Arseniyadis, Siméon
Abstract: Arylcarbinol‐ and benzyl‐tethered octalin‐diols (1 /1′ ), which differ only by the C11 substitution at the angular position, were transformed selectively into original scaffolds of high complexity through a two‐step protocol. Overall, the (11 S *) configuration ensures an intramolecular Friedel–Crafts‐type C13–C4 bonding through a domino process triggered by oxidative cleavage, whereas the (11 R *) configuration allows for a Marson‐type Friedel–Crafts C13–C2 bonding through an intramolecular nucleophilic acetal opening. Abstract : A two‐step protocol for rapid generation of molecular complexity by an efficient combination of oxidative cleavage/nucleophilic acetal opening sequences; from octalindiols to original tetrahydrofuran‐centered scaffolds such as furofurans, octahydroanthracenes, spirocyclohexyltetralins, or to bicyclo[6.6.7] ring systems.